The Growth of the Cameroonian Public Sector: An Analysis from Adolph Wagner's Approach - Mengnjo, Thomas; Uchon, Fidelis (American Journal of Leadership and Governance, 2024)
Purpose: This article sheds light on the determining factors accountable for the growth of the Cameroonian public sector from Adolph Wagner's Perspective. Methodology: To realize the objective, data were obtained through documentary and secondary sources, such as the World Bank Reports and other relevant documents. Information obtained was contently analysed, while numeric information was presented in percentages and tables. Findings: Using Adolph Wagner's Approach, findings showed that the size of the Cameroon public service has grown in size due to political, economic and social determinants. Politically, it has increased due to political instability and voter maximization behaviours by politicians; economically, it is due to the demand for public and merit goods, the fight against unemployment, and the government's regulatory role in the economy. Socially, it is accounted for by increasing population growth and demand for social services. Unique Contribution to Theory, Practice and Policy: This article from the Theoretical Standpoint of Adolph Wagner's perspective has resolved that the size of the Cameroonian public service has increased in size over the years as a result of political and socio-economic undertones, which to a greater extent has not been efficient service delivery. It is from this perspective that it is highly recommended that, there is an urgent need for accountability and responsiveness to be imbibed into the Cameroon public to ensure efficient delivery of goods and services to the public.